Metal–Organic Framework‐Derived Materials for Sodium Energy Storage. Issue 3 (11th December 2017) - Zou, Guoqiang; Hou, Hongshuai; Ge, Peng; Huang, Zhaodong; Zhao, Ganggang; Yin, Dulin; Ji, Xiaobo
Abstract: Recently, sodium‐ion batteries (SIBs) are extensively explored and are regarded as one of the most promising alternatives to lithium‐ion batteries for electrochemical energy conversion and storage, owing to the abundant raw material resources, low cost, and similar electrochemical behavior of elemental sodium compared to lithium. Metal–organic frameworks (MOFs) have attracted enormous attention due to their high surface areas, tunable structures, and diverse applications in drug delivery, gas storage, and catalysis. Recently, there has been an escalating interest in exploiting MOF‐derived materials as anodes for sodium energy storage due to their fast mass transport resulting from their highly porous structures and relatively simple preparation methods originating from in situ thermal treatment processes. In this Review, the recent progress of the sodium‐ion storage performances of MOF‐derived materials, including MOF‐derived porous carbons, metal oxides, metal oxide/carbon nanocomposites, and other materials (e.g., metal phosphides, metal sulfides, and metal selenides), as SIB anodes is systematically and completely presented and discussed. Moreover, the current challenges and perspectives of MOF‐derived materials in electrochemical energy storage are discussed. Abstract : Metal‐organic framework (MOF)‐derived materials are widely utilized as sodium ion battery anodes owing to their fast mass transport and simple preparation methods. Recent progress in MOF‐derived materials, including MOF‐derived porous carbons, metal oxides, metal oxide/carbon nanocomposites, and other materials (e.g., metal phosphides, metal sulfides, and metal selenides), for sodium energy storage is presented and discussed.